METHODS OF INCREASING THE STUDENTS ’ COMPETENCE THROUGH THE CREATIVITY OF RUSSIAN COMPOSERS IN MUSIC LESSONS - Fozilov Qahramon Madaminovich (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
in this article, the lessons of “music culture " are taught about the formation and upbringing of aesthetic tastes of students through the works of World Music, Russian classical composers. The positive effect of classical music on the education of students is very illuminated.